A quasi-experimental study to determine the effects of a multifaceted educational intervention on hand hygiene compliance in a radiography unit. Issue 1 (December 2016) - O'Donoghue, Margaret; Ng, Suk-Hing; Suen, Lorna; Boost, Maureen
Abstract Background Whilst numerous studies have investigated nurses' compliance with hand hygiene and use of alcohol-based hand rub (ABHR), limited attention has been paid to these issues in allied health staff. Reports have linked infections to breaches in infection control in the radiography unit (RU). With advances in medical imaging, a higher proportion of patients come into contact with RU staff increasing the need for good hand hygiene compliance. This study aimed to evaluate effectiveness on compliance of an intervention to improve awareness of hand hygiene in the RU of a district hospital. Methods A quasi-experimental study design including questionnaires assessing knowledge and attitudes of hand hygiene and direct observation of participants was used to evaluate an educational programme on hand hygiene of the RU of a large district hospital. All healthcare workers (HCW), comprising 76 radiographers, 17 nurses, and nine healthcare assistants (HCA), agreed to participate in the study. Of these, 85 completed the initial and 76 the post-test anonymous questionnaire. The hand hygiene compliance of all 102 HCW was observed over a 3-week period prior to and after the intervention. The 2-month intervention consisted of talks on hand hygiene and benefits of ABHR, provision of visual aids, wall-mounted ABHR dispensers, and personal bottles of ABHR. Results Before the intervention, overall hand hygiene compliance was low (28.9 %). Post-intervention, compliance with hand hygiene increased to 51.4 %. This improvement was significant for radiographers and HCA. Additionally, knowledge and attitudes improved in particular, understanding that ABHR can largely replace handwashing and there is a need to perform hand hygiene after environmental contact. The increased use of ABHR allowed HCW to feel they had enough time to perform hand hygiene. Conclusions The educational intervention led to increased awareness of hand hygiene opportunities and better acceptance of ABHR use. The reduced time needed to perform hand rubbing and improved access to dispensers resulted in fewer missed opportunities. Although radiographers and other allied HCW make frequent contact with patients, these may be mistakenly construed as irrelevant with respect to healthcare associated infections. Stronger emphasis on hand hygiene compliance of these staff may help reduce infection risk.